2003
DOI: 10.1159/000075733
|View full text |Cite
|
Sign up to set email alerts
|

A new contribution to the integration of human and porcine genome maps: 623 new points of homology

Abstract: In this study we examined homologies between 1,735 porcine microsatellites and human sequence. For 1,710 microsatellites we directly used the sequence flanking the repeat available in GenBank. For a set of 305 microsatellites, a BAC library was screened and end-sequencing provided 461 additional sequences. Altogether 2,171 porcine sequences were tentatively aligned with the sequence of the human genome using the fasta program. Human homologies were observed for 652 microsatellite loci and porcine chromosome as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…These results are in perfect accordance with Robic et al (2003), who reported the corresponding locations of 623 porcine microsatellites on the human genome, comprising those found in this study with the highest LOD scores. These results are in perfect accordance with Robic et al (2003), who reported the corresponding locations of 623 porcine microsatellites on the human genome, comprising those found in this study with the highest LOD scores.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in perfect accordance with Robic et al (2003), who reported the corresponding locations of 623 porcine microsatellites on the human genome, comprising those found in this study with the highest LOD scores. These results are in perfect accordance with Robic et al (2003), who reported the corresponding locations of 623 porcine microsatellites on the human genome, comprising those found in this study with the highest LOD scores.…”
Section: Discussionsupporting
confidence: 93%
“…Second, we shall present the studies aimed at characterizing the metabolic pathways involved and the physiological methodologies used to identify candidate genes. In order to better confront the two approaches, we provide in Table I data on the genes cited in this review with their putative position in the pig genome deduced from their location on the human physical map (http://www.ensembl.org/Homo_sapiens/index.html) and the comparative pig/human map established by Robic et al [34] (http://www2.toulouse.inra.fr/lgc/pig/msat/). Lastly, we shall give some perspectives on the use of these various strategies to identify genes involved in such complex traits.…”
Section: Introductionmentioning
confidence: 99%
“…Updated summary of the data known for the genes cited in this paper. The expected location on the porcine linkage map is deduced from the position in the human genome and the pig/human comparative map proposed by Robic et al [34]. For the CYP2E…”
Section: Introductionmentioning
confidence: 99%
“…However, comparative mapping of human and porcine chromosome regions might allow us to postulate some candidate genes that might eventually be responsible for predisposition to AA (see Table 4). The comparative maps established by Goureau et al (1996Goureau et al ( , 2000, Shi et al (2001), and Robic et al (2003) suggest that the region SSC 1q18-q21 flanked by markers SW1621 and SW1902 maps to three different human chromosomal regions: HSA 15q26, HSA 14q22, and HSA 9q21-q34. Our own BLAST searches comparing the porcine flanking sequence of SW1621 and SW1902 to the human genome sequence suggest that it is homologous to HSA 9q34.4.…”
Section: Discussionmentioning
confidence: 99%
“…for genotyping. Olaf Bininda-Emonds, funded by Bundesministerium fü r Bildung und Forschung (Federal Ministery of Education and Research), provided (Goureau et al 1996(Goureau et al , 2000Shi et al 2001;Robic et al 2003).…”
Section: Discussionmentioning
confidence: 99%